Mental health status of workers in selected tea estates, Tamil Nadu, India - Ashwini, G.S.; Ramesh, Naveen; Navya, C.J.; Joy, J.; Thomas, A.; Jyoti, S. (International Journal of Occupational Safety and Health, 2017)
Introduction: The prevalence of mental illnesses among industrial workers ranged between 14% - 51%, which is more than that of the general population. Individual’s psychosocial functioning has an impact on the work efficiency and hence the current study was undertaken to screen workers in tea plantations. Objective: To document the prevalence of probable mental illness and its associated factors among workers in selected tea estates in South India. Methodology: A cross sectional study was done in two tea estates in Tamil Nadu from March to May 2012. The General Health Questionnaire (GHQ) 28 was used to screen for mental health status. Socio-demographic details, work profile and associated risk factors were also documented. Results: Among the 400 subjects interviewed, 75.5% were females. The mean age was 43.21 (±7.47) years and the mean work experience was 21.38 (±9.31) years. In this study 12.8% subjects screened positive for probable mental illness and 1%, 1%, 0.2% and 1.5% screened positive for the domains of somatic symptoms, anxiety/insomnia, social dysfunction and severe depression respectively. Workers who screened positive for probable mental illness had availed significantly greater duration of leave in the previous year. There was no significant association of mental illness with age, gender, marital status, substance abuse, designation, co-morbidity and stressful life events. Conclusion: The prevalence of probable mental illness was similar to other occupational settings. Management of the associated risk factors may improve one’s work efficiency and productivity.